Buster Moon Projections: How Cartoon Characters Activate Psychoanalytic Defense Mechanisms in "Sing (2016)" - Alamsyah, Fikri; Sari, Retno Purwani; Dewi, Nenden Rikma (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2024)
This research aims to examine the projection of the character Buster Moon in the animated film "Sing" (2016) using a psychoanalytic theory approach, especially defense mechanisms. Buster Moon, an optimistic and persistent koala, struggles to save his theater from bankruptcy by holding a singing competition. This study explores how the character reflects and activates defense mechanisms by projection, both within himself and in interactions with other characters. Denial can be seen in his continued disregard for difficult financial realities. Projection is demonstrated through the way he handles personal fears and failures by focusing on the dreams and ambitions of others. Through this analysis, the author reveals how Buster Moon as a cartoon character functions not only as an entertainer, but also as a reflection of human defense mechanisms, providing insight into how animated films can function as a medium for understanding psychological dynamics in life. Keywords: Film, Projection, Defense Mechanism, Psychoanalysis